Developing Preferences and Dislikes to Improve Profile Matching - Nirmala, Adityas; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2014)
Abstract - PT Krakatau Steel (Persero) Tbk. (PT KS) is the largest integrated steel company in Indonesia, has a very strong Vision that is becoming an Integrated Steel Company with a competitive advantage to continually grow and evolve into a leading company in the world. In realizing its vision and mission, PT KS realize the necessary building strong leadership, not just rely on the presence of a leader by chance, but build a strong foundation for creating a strong leadership system. PT KS has launched Talent Management in 2009 but is still limited in concept fragmentary and partial implementation. Components and basic infrastructure such as catalogs competence, competency, and individual competencies and career path has been owned by PT KS, so it can be used in the gap analysis process competency required for program development including mutations and promotion process. In determining candidates in the process of promotion and transfer, the necessary stages of profile matching to see the level of compatibility between the required profile with profiles of individual candidates. Compliance is increasingly exaggerated level when equipped with Preferences and Dislikes of data, which describe the position of a preferred position or positions that are not favored position. With this improvement, the level of success in promotion and transfer process becomes higher. This will take effect in improving organizational performance.Â Key Word: Talent Management, PT Krakatau Steel (Persero) Tbk., Personal Development, Profile Matching, Preferences, Dislikes.